Cardiovascular risk factors and body fat distribution in brazilians aged 80 years or over - Gomes, Igor C.; Dos Santos, Vanessa R. [UNESP]; Christofaro, Diego G.D. [UNESP]; Fernandes, Rômulo A. [UNESP]; Bueno, Denise R. [UNESP]; Júnior, Ismael F Freitas [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2016)
Study design: Cross-sectional study. Objective: To analyze the presence of cardiovascular risk factors (CRFs) according to the pattern of body fat distribution, in Brazilians aged 80 years or over. Methods: The sample consisted of 113 subjects, of 83.4 years, of both sexes. The percentages of total and abdominal body fat, hypertension and lipid profile were used for characterization of CRFs. The chisquare test was used to assess proportions of CRFs and the Mann-Whitney test was used to compare the results of adiposity. Results: Eutrophic subjects presented lower triglycerides (p=0.017), total cholesterol (p=0.001) and prevalence of both hypertension (p=0.003) and hypertriglyceridemia (p=0.007). Subjects with higher abdominal adiposity presented higher total cholesterol (p=0.026) and prevalence of hypertriglyceridemia (p=0.011) and hypercholesterolemia (p=0.026) than those with no excess abdominal adiposity. Those with excess fat (total, abdominal or both), with the exception of glucose (p=0.877), presented a high prevalence of CRFs. Those with both types of excess fat presented differences, with a higher prevalence level when compared to those with only one or neither of the excesses. Conclusion: Obesity, whether abdominal or total, is similarly associated with CRFs in subjects aged 80 years and over.
Keywords: Cardiovascular Diseases; Elderly; Epidemiology; Obesity